Quasilinear, Overlapping-Generations Economies - Joaquim Silvestre (University of California, Department of Economics, 1995)
The quasilinearity assumption (informally speaking, the assumption that utility is linear in the numeraire good, or that income effects are absent from the demand of nonnumeraire goods) makes surplus analysis exact in economies where all agents are contemporaneous. Efficiency is then eqivalent to the maximization of social surplus: we shall refer to this fact as the ""global equivalence principle."" But in many interesting applications the assumption of a single generation is not realistic, e.g., in long lived investment programs or in the use of environmental resources. This paper provides an extension of traditional surplus analysis to a world of multiple, overlapping generations. In the single generation case, efficiency is equivalent to the maximization of social surplus provided that no lower bounds exist in the final holdings of numeraire. If such lower bounds do exist, then one could have efficient allocations where social surplus is not at its maximum. Figures 1 and 2 illustrate. Let there be one generation and two people, Person 1 and Person 2.
Keywords: 330